Catalytic fast pyrolysis of Arundo donax in a two-stage fixed bed reactor over metal-modified HZSM-5 catalysts. (January 2022) - Guo, Xiang; Yang, Huijun; Wenga, Terrence; Zhang, Rui; Liu, Bin; Chen, Guanyi; Hou, Li'an
Abstract: Various types of mono- and bi-metallic modified HZSM-5 catalysts such as Mo-, Fe-, Zn-, Cu-, Mo–Fe-, Mo–Zn-, and Mo–Cu-modified HZSM-5 were prepared via impregnation and were characterized by scanning electron microscope (SEM), inductively coupled plasma atomic emission spectrometry (ICP-AES), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) and pyridine adsorption infrared spectroscopy (Py-IR) analysis. Online catalytic upgrading of Arundo donax pyrolysis vapors was performed using modified zeolite catalysts in a two-stage fixed bed reactor to investigate the catalytic performance. Results showed that loading of Mo, Fe, Zn and Cu were well-dispersed, the channels and acidity of zeolites were modified. Impregnation of HZSM-5 with metals resulted in relatively lower yield of oxygenates and nitrogen-containing compounds in bio-oil as compared to the reference condition without catalyst. Moreover, the addition of metals significantly favored the catalytic selectivity towards aromatics especially monocyclic aromatic hydrocarbons (MAHs). Mo-M/HZSM-5 catalysts was the best catalyst and exhibited the optimal de-oxygenation potential (from 62.66% to 18.03%), denitrification (from 6.53% to 0.43%) and produced maximum MAHs content approximately 28.77%. Among the bimetallic modified zeolite catalysts, Mo–Zn/HZSM-5 exhibited strong catalytic effect in oxygen-free aromatization of the mixed pyrolysis vapors containing methane and propane. In the presence of Mo–Zn/HZSM-5 catalyst, the content of oxygen in bio-oil decreased from 36.07 wt% to 15.05 wt%, and the calorific value reached a maximum value of 34.12 MJ kg −1 . Mo–Zn/HZSM-5 has been identified as a superior catalyst for improving the value of Arundo donax pyrolysis to make bio-oil. Highlights: Mono and bimetallic loaded HZSM-5 was used for Arundo donax CFP in two-stage system. Aromatization performance and MAHS selectivity was obviously improved through CFP. Mo–Zn/HZSM-5 optimally improved the pyrolysis of Arundo donax to make bio-oil. Co-doping of Mo and Zn on HZSM-5 enhanced the aromatization of CH4 and propane.